2021
DOI: 10.1101/2021.07.28.454147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perception of structurally distinct effectors by the integrated WRKY domain of a plant immune receptor

Abstract: Plants use intracellular immune receptors (NLRs) to detect pathogen-derived effector proteins. The Arabidopsis NLR pair RRS1-R/RPS4 confers disease resistance to different bacterial pathogens by perceiving structurally distinct effectors AvrRps4 from Pseudomonas syringae pv. pisi and PopP2 from Ralstonia solanacearum via an integrated WRKY domain in RRS1-R. How the WRKY domain of RRS1 (RRS1WRKY) perceives distinct classes of effector to initiate an immune response is unknown. We report here the crystal structu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 70 publications
3
15
0
Order By: Relevance
“…Furthermore, the plant immunity R genes are expanded in plant genomes and share many characteristics in common with the C. elegans pals gene family, although they are not homologs (4). In particular, there are similarities in gene expression regulation, protein-protein interactions and phenotypes between the pals-22/pals-25 pair and the R gene pair RPS4/RRS1 in the plant Arabidopsis thaliana (23-26). Importantly, R genes regulate a switch between growth and defense, similar to pals genes (1-4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the plant immunity R genes are expanded in plant genomes and share many characteristics in common with the C. elegans pals gene family, although they are not homologs (4). In particular, there are similarities in gene expression regulation, protein-protein interactions and phenotypes between the pals-22/pals-25 pair and the R gene pair RPS4/RRS1 in the plant Arabidopsis thaliana (23-26). Importantly, R genes regulate a switch between growth and defense, similar to pals genes (1-4).…”
Section: Discussionmentioning
confidence: 99%
“…(which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.It is made The copyright holder for this preprint this version posted January 18, 2023. ; https://doi.org/10.1101/2023.01.15.524171 doi: bioRxiv preprintgene family, although they are not homologs (4). In particular, there are similarities in gene expression regulation, protein-protein interactions and phenotypes between the pals-22/pals-25 pair and the R gene pair RPS4/RRS1 in the plant Arabidopsis thaliana(23)(24)(25)(26). Importantly, R genes regulate a switch between growth and defense, similar to pals genes(1)(2)(3)(4).The presence of antagonistic paralogs in pals and R gene families highlights the importance of maintaining the balance between immunity and development.…”
mentioning
confidence: 99%
“…pisi and PopP2 from Ralstonia solanacearum (Le Roux et al, 2015 ; Narusaka et al, 2009 ). Interestingly, crystal structures of RRS1 WRKY in complex with AvrRps4 or PopP2 revealed that the two effectors target the same region of RRS1 WRKY (Mukhi et al, 2021 , Zhang et al, 2017b ) (Figure 2c ). In rice, two CNL pairs, RGA4/RGA5 and Pik‐1/Pik‐2, use the integrated heavy metal‐associated (HMA) domain in the sensors RGA5 and Pik‐1, respectively, to directly recognize cognate effectors.…”
Section: Nlr Recognition Of Effectorsmentioning
confidence: 99%
“…AvrRps4 is cleaved in planta into two fragments (Sohn et al, 2009). The Cterminal fragment forms an antiparallel a-helical coiled coil structure including a surface-exposed electronegative domain that makes a binding interface with the WRKY DNAbinding domain of RRS1-R (Mukhi et al, 2021;Sohn et al, 2012). The N-terminal fragment is sufficient to activate immunity in lettuce (Halane et al, 2018).…”
Section: Introductionmentioning
confidence: 99%